2008
DOI: 10.1291/hypres.31.1045
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Increases in Blood Pressure by Dynamic Resistance Exercise in Middle-Aged Men

Abstract: The present study was performed to test the hypothesis that the blood pressure (BP) response to resistance exercise in middle-aged men with stiffening arteries is greater than that in young men with compliant arteries. The BP responses to acute dynamic resistance exercise (leg press) at individual relative (low, moderate and high) and absolute intensities were investigated in both young and middle-aged men. A total of 21 sedentary healthy normotensive men, 21-25 years of age (young) and 41-59 years of age (mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…These values range from 2 to 17 and from 2 to 7 mm Hg for systolic and diastolic BP, respectively, in aerobic exercises [4,32]. For resistance exercises, most studies prove a reduction of 2-13 mm Hg for systolic BP and 2-7.9 mm Hg for diastolic BP [23,[32][33][34][35][36]. On the basis of the PEH values found in this study, the effectiveness and possibility are evident of applying FT in order to promote PEH in borderline hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…These values range from 2 to 17 and from 2 to 7 mm Hg for systolic and diastolic BP, respectively, in aerobic exercises [4,32]. For resistance exercises, most studies prove a reduction of 2-13 mm Hg for systolic BP and 2-7.9 mm Hg for diastolic BP [23,[32][33][34][35][36]. On the basis of the PEH values found in this study, the effectiveness and possibility are evident of applying FT in order to promote PEH in borderline hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Muller et al (24) had participants perform isometric handgrip and found that older adults experience lower rate-pressure product and coronary blood flow velocity responses. Unlike isometric exercise, the blood pressure responses to dynamic resistance exercise are attenuated in middle-aged compared with young adult males (16). Likewise, rhythmic handgrip during a period of experimentally lowered blood flow results in an attenuated MSNA and blood pressure response with aging (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing age has the potential to impair autonomic cardiovascular regulation (16,18,21,28). For example, Markel et al (18) reported attenuated sympathetic and blood pressure responses in older adults during blood flow restricted rhythmic exercise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Physical exercise has been reported to be an important and efficient nonpharmacological strategy for controlling blood pressure (BP) and for preventing and treating cardiovascular diseases, such as arterial hypertension (Anunciação & Polito, 2011;Kawano, Nakagawa, Onodera, Higuchi, & Miyachi, 2008;Polito, Farinatti, Lira, & Nobrega, 2007).…”
Section: Introductionmentioning
confidence: 99%